Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1046/j.1365-2443.2001.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

PKC1, a protein kinase C homologue of Saccharomyces cerevisiae, participates in microtubule function through the yeast EB1 homologue, BIM1

Abstract: Background: RSC is a chromatin-remodelling complex of Saccharomyces cerevisiae and essential for growth. Its catalytic subunit is encoded by the NPS1/STH1 gene. At the present time, little is known regarding the cellular function of RSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 40 publications
(57 reference statements)
1
28
0
Order By: Relevance
“…PKCs have been associated with MTs in many cell types (Kiley and Parker, 1995;Garcia-Rocha et al, 1997;Hosotani et al, 2001;Kabir et al, 2001;Szalay et al, 2001;Nakhost et al, 2002), and, in yeast, PKC1 regulates the function of MTs through BIM1, the yeast EB1 homologue (Hosotani et al, 2001). As shown in this study, however, PKC inhibition by Gö-6976 had no effect on the recruitment of EB1 upon cell membrane disruption.…”
Section: Discussionmentioning
confidence: 40%
“…PKCs have been associated with MTs in many cell types (Kiley and Parker, 1995;Garcia-Rocha et al, 1997;Hosotani et al, 2001;Kabir et al, 2001;Szalay et al, 2001;Nakhost et al, 2002), and, in yeast, PKC1 regulates the function of MTs through BIM1, the yeast EB1 homologue (Hosotani et al, 2001). As shown in this study, however, PKC inhibition by Gö-6976 had no effect on the recruitment of EB1 upon cell membrane disruption.…”
Section: Discussionmentioning
confidence: 40%
“…A rom2⌬ mutant and a pkc1(Ts) mutant but not an mpk1⌬ mutant were found to be hypersensitive to the microtubule antagonists benomyl and thiabendazole, respectively (124,201). Conversely, overexpression of Pkc1 confers thiabendazole resistance on wildtype cells (124). Interestingly, these authors also demonstrated that a pkc1(Ts) mutant displays a G 2 delay and aberrant nuclear positioning in a fraction of the cells at semipermissive temperature, supporting the notion that Pkc1 plays a role in microtubule or SPB function.…”
Section: Nuclear Functions Of Pkc1mentioning
confidence: 99%
“…A rom2⌬ mutant and a pkc1(Ts) mutant but not an mpk1⌬ mutant were found to be hypersensitive to the microtubule antagonists benomyl and thiabendazole, respectively (124,201). Conversely, overexpression of Pkc1 confers thiabendazole resistance on wildtype cells (124).…”
Section: Nuclear Functions Of Pkc1mentioning
confidence: 99%
“…First, conditional pkc1 mutants undergo cell lysis uniformly with small buds and duplicated DNA, but prior to spindle pole body (SPB) separation (Levin et al 1990;Levin and Bartlett-Heubusch 1992). Second, under growth conditions in which cell lysis was prevented by osmotic support, a conditional pkc1 mutant was shown to linger at G 2 /M, a phenotype that was attributed to a delay in spindle elongation (Hosotani et al 2001). Third, several studies have revealed genetic connections between Pkc1 and the chromatin remodeling complex called RSC (reviewed in Levin 2005), which serves a critical function in the progression from G 2 to mitosis.…”
Section: Rho1 Activation During Cytokinesismentioning
confidence: 99%